2002
DOI: 10.1021/bc0255900
|View full text |Cite
|
Sign up to set email alerts
|

Tat-Conjugated Synthetic Macromolecules Facilitate Cytoplasmic Drug Delivery To Human Ovarian Carcinoma Cells

Abstract: We have synthesized N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-cell penetrating peptide Tat conjugates and evaluated their subcellular distribution in A2780 human ovarian carcinoma cells by confocal fluorescence microscopy and subcellular fractionation. Our data indicate the transport of these conjugates by a single Tat molecule to both the cytoplasm and nucleus via a nonendocytotic and concentration independent process. The uptake was observed to occur within 3 min, as confirmed by live cell microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 19 publications
(20 reference statements)
2
87
0
1
Order By: Relevance
“…The one most commonly employed is trypsin treatment, which removes the surface-bound fusion proteins and reduces the chances of nonspecific migration of proteins upon fixation of cells during immunostaining. In addition, some studies have shown successful transduction of PTD-fusion proteins into cells without fixation [47,98,[158][159][160][161]. Further, many of these studies have also shown biological effects upon treatment with PTD-fusion proteins, which could be due to the interactions with surface receptors [162] or due to the release of proteins from lysosomes into the cytoplasm and nucleus.…”
Section: Validation Of True Ptd-mediated Protein Transductionmentioning
confidence: 99%
“…The one most commonly employed is trypsin treatment, which removes the surface-bound fusion proteins and reduces the chances of nonspecific migration of proteins upon fixation of cells during immunostaining. In addition, some studies have shown successful transduction of PTD-fusion proteins into cells without fixation [47,98,[158][159][160][161]. Further, many of these studies have also shown biological effects upon treatment with PTD-fusion proteins, which could be due to the interactions with surface receptors [162] or due to the release of proteins from lysosomes into the cytoplasm and nucleus.…”
Section: Validation Of True Ptd-mediated Protein Transductionmentioning
confidence: 99%
“…Most studies involving PTDmediated cellular uptake have been carried out with Tat peptide. Tat-modified nanoparticles, such as cross-linked iron oxide for cell tracking by magnetic resonance [18] or polymeric drug carriers [19] showed improved uptake properties when compared to unmodified particles. The Tat peptide was also used to investigate PTD-mediated liposome uptake.…”
mentioning
confidence: 99%
“…To understand if both intracellular phenotypes are two distinct intermediate stages of the same process or indicate different uptake routes, we monitored the cytoplasmic and nucleolar localization of RRPs upon inhibition of endocytosis. In addition to TAT, we used the peptide PTD 4 , which is an artificial, more amphipathic CPP with a reduced number of arginines and increased ␣-helical content compared with TAT (29). Most importantly, to suppress endocytic pathways, we restricted ourselves to the usage of genetically inducible systems, knock-out (KO) cell cultures, or physical methods, thus avoiding any potential side effects of chemical inhibitors of endocytosis.…”
mentioning
confidence: 99%